Modulation of active oxygen forms production by circulating phagocytes and clinical efficacy of glucocorticoid treatment in patients with systemic lupus erythematosus - N. V. Romanova (Научно-практическая ревматология, 2005)
Objective. To study glucocorticoids (GC) clinical efficacy and their influence on active oxygen forms production by circulating phagocytes (neutrophils and monocytes) in pts with systemic lupus erythe- matosus(SLE) receiving traditional treatment with low and intermediate doses of GC so as with pulse- therapy with mega doses of GC. Material and methods. SLE pts were randomly allocated in two groups (15 pts in each). Group 1 was treated with methylprednisolone (MP) 20-40 mg/day during 3 weeks and Group 2 pts received MP mega doses 10 mg/kg as intravenous drip-feed during 3 days with subsequent decrease to maintaining doses. Luminol-dependent and lucigenin-dependent whole blood leucocytes chemiluminescence separately with neutrophils and monocytes so as phagocytic indices and circulating immune complexes (C1C) level were evaluated Results. SLE pts showed increase of active oxygen forms spontaneous production and CIC level so as decrease of induced chemiluminiscence, phagocytes stimulation coefficient and phagocytosis indices. Treatment with intermediate GC doses provided decrease of active oxygen forms synthesis by neu- trophiles and monocytes so as to cell stimulation coefficients increase along with improvement of their digesting capability and decrease of CIC level